2021
DOI: 10.1088/1402-4896/ac40d6
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological model with time varying deceleration parameter in F(R, G) gravity

Abstract: In this paper, we study the dynamical behaviour of the universe in the F (R, G) theory of gravity, where R and G respectively denote the Ricci scalar and Gauss-Bonnet invariant. Our wide analysis encompasses the energy conditions, cosmographic parameters, Om(z) diagnostic, stability and the viability of reconstructing the referred model through a scalar field formalism. The model obtained here shows the quintessence like behaviour at late times.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Moreover, with the suitable choice for F leading to F (R, G) = R, one recovers Einstein's GR as well. Thus, one can see that this modified gravity theory being the generalized version of both F (R) and F (G) gravity theories can offer some appealing consequences and very soon of its introduction, F (R, G) gravity theory received significant attention in the community [573,608,623,625,[630][631][632][633][634][635][636][637][638][639][640][641][642][643][644][645].…”
Section: G F (R G) Gravitymentioning
confidence: 99%
“…Moreover, with the suitable choice for F leading to F (R, G) = R, one recovers Einstein's GR as well. Thus, one can see that this modified gravity theory being the generalized version of both F (R) and F (G) gravity theories can offer some appealing consequences and very soon of its introduction, F (R, G) gravity theory received significant attention in the community [573,608,623,625,[630][631][632][633][634][635][636][637][638][639][640][641][642][643][644][645].…”
Section: G F (R G) Gravitymentioning
confidence: 99%
“…Subsequently, Singh et al [46] explored the bulk viscous FRW cosmos and demonstrated that the universe's current acceleration is due to the contribution of viscosity. There have been several excellent studies in the literature for confining the various homogeneous and isotropic universe features in various gravitational theories [47][48][49][50][51]. In the present manuscript, we have explored an accelerating cosmic model of a hybrid universe in f (R, T ) theory.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the cosmographic parameters are investigated. In the case of an accelerated expanding Universe, the deceleration parameter q should take negative values and tend to the value q = −1 [39,40]. Partially, based on cosmographic parameters, the values of the statefinders are calculated [41,42].…”
Section: Introductionmentioning
confidence: 99%